Problems Arising In Increasing The Export Potential Of Agricultural Products And Their Solutions (The Peerian Journal, 2024)
The agricultural sector is a cornerstone of economic development and plays a pivotal role in ensuring food security globally. Many countries, especially those in developing regions, heavily rely on agricultural exports as a means to boost their economies and improve livelihoods. However, numerous challenges hinder the ability of agricultural producers to capitalize on international markets effectively. This article aims to identify the primary problems affecting the export potential of agricultural products and to propose actionable solutions to enhance their competitiveness.